Dear land surveyors, veterans of the branch! - Tretiak, A. (Land Management, Cadastre and Land Monitoring, 2017)
On behalf of the All-Ukrainian public organization "Union of Land Managers of Ukraine", we congratulate you on the professional holiday "The Day of the Land Surveyor"!